A study on the main features of short jokes and implications for teaching speaking to students of grade 12 at Ngoc Tao Upper Secondary School - Phan, Thi An (ĐHNN, 2017)
English jokes tend to cause problems to language learners because of their linguistic, cultural and socio features. In this study, the author examined the corpus of 100 simple jokes given in the book “America one and two liners” and some searched from websites to investigate the linguistic features of English short jokes. The study is based on theories of humour. From the findings of linguistic features of short jokes, the author suggests some activities for teaching speaking skill at a high school with the aim to use jokes as a useful material to motivate students